2021
DOI: 10.1093/jmammal/gyab080
|View full text |Cite
|
Sign up to set email alerts
|

Winter roosting ecology of tricolored bats (Perimyotis subflavus) in trees and bridges

Abstract: Tricolored bats (Perimyotis subflavus) that roost in subterranean hibernacula have experienced precipitous declines from white-nose syndrome (WNS); however, understudied populations also use during winter non-subterranean roosts such as tree cavities, bridges, and foliage. Our objectives were to determine winter roost use by tricolored bats in an area devoid of subterranean roosts, determine roost microclimates to relate them to growth requirements of the fungal causal agent of WNS, and determine habitat facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However, warmer temperatures in southern hibernacula resulting in faster fungal growth rates could counter this effect. In the southeastern U.S., temperatures in hibernacula used by tricolored bats are often in the optimal range for P. destructans growth (i.e., 12.5–15.8°C) (Lutsch, 2019 ; Meierhofer et al, 2019 ; Newman et al, 2021 ; Sirajuddin, 2018 ) and the relatively warm hibernacula temperatures in the southeast may explain the high mortality rates observed in this region (>90%) since the arrival of WNS (Pete Pattavina, pers. comm.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, warmer temperatures in southern hibernacula resulting in faster fungal growth rates could counter this effect. In the southeastern U.S., temperatures in hibernacula used by tricolored bats are often in the optimal range for P. destructans growth (i.e., 12.5–15.8°C) (Lutsch, 2019 ; Meierhofer et al, 2019 ; Newman et al, 2021 ; Sirajuddin, 2018 ) and the relatively warm hibernacula temperatures in the southeast may explain the high mortality rates observed in this region (>90%) since the arrival of WNS (Pete Pattavina, pers. comm.).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the tricolored bat was one of the most common bat species in southern hibernacula (Meierhofer et al, 2019 ; Perry & Jordan, 2020 ; Stevens et al, 2017 ). In addition to hibernating in underground structures such as caves, mines, and tunnels, they also use above‐ground structures such as bridges, culverts, storm drains, water wells, and trees (Ferrara & Leberg, 2005 ; Fujita & Kunz, 1984 ; Goering, 1954 ; Newman et al, 2021 ; Sandel et al, 2001 ; Sasse et al, 2011 ). In northern portions of their range, tricolored bats that hibernate in caves and mines usually select the warmest (7.3–11.8°C) and most humid sites within the hibernaculum (Briggler & Prather, 2003 ; Kurta & Smith, 2014 ; Raesly & Gates, 1987 ), but in Florida, where caves are warmer, they select cooler caves (13.0°C; Smith et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Newman et al . (2021) discovered P. subflavus roosting on metal, ribbed sheets bolted to a bridge ceiling as well as on concrete I-beams. As seen in natural cave roosts, roost locations selected at bridges can vary between species, time of year, and seasonally.…”
Section: Resultsmentioning
confidence: 99%
“…Bats population in Sanghyang Kenit was distributed from twilight to dark zones, which generated guano piles on the cave floor. Commensurate with cave crickets, bats prefer humid and dark places for their roosting sites (Furey & Racey 2016;Lizarro et al 2020;Newman et al 2021). The measurement of soil pH showed that twilight and dark zones have more acidic pH than the entrance.…”
Section: Habitat Preference Based On Environmental Parametersmentioning
confidence: 99%